Sub-epithelial connective tissue graft and enamel matrix derivative in the management of a localized gingival recession defect: A case report - Akram, Z.; Khawaja, N.A.; Rashid, H.; Vohra, F. (Elsevier, 2016)
Within the past 20 years, clinicians have successfully performed mucogingival surgeries to restore periodontal defects. This article describes the application of enamel matrix derivative (EMD) in combination with connective tissue graft (CTG) for the repair of localized mucogingival defect. The procedure was performed to observe the clinical success of autogenous CTG in the treatment of moderate facial recession defect combined with the usage of an EMD. The management involved scaling and root planning, root surface conditioning, elevation of full-thickness flap, application of EMD, shaping and application of CTG at the recession site. Eight-month observations showed root coverage of 3 mm (>75%) with attachment level gain of 4 mm and a gingival margin that was harmonious with adjacent teeth. From a clinical observation, it emerges that root coverage and soft tissue attachment is possible with the use of autogenous CTG in combination with EMD in the management of moderate gingival recession defects.